IMPROVING STUDENTS’ COLLABORATION SKILLS THROUGH THE TEAMS GAMES TOURNAMENT MODEL ON THE TOPIC OF EARTH AND THE SOLAR SYSTEM - Siti Muliana; Syaffa Diah Aulia Rahma; Pramudya Dwi Aristya Putra (STKIP Citra Bakti, 2026)
The low level of students’ collaboration skills in science learning remains a common issue in schools, particularly during group discussions that do not actively engage all students. This condition highlights the need for a learning model capable of creating an active, interactive, and collaborative learning environment in line with the demands of 21st-century skills. This study aimed to improve students’ collaboration skills through the implementation of the Teams Games Tournament (TGT) learning model in the topic of Earth and the Solar System. The study employed a Classroom Action Research method based on the Kemmis and McTaggart model, conducted in two cycles consisting of planning, action, observation, and reflection stages. The research subjects were 32 students of class VII C at SMP Negeri 11 Jember. Data were collected through observation, peer assessment, and field notes. The data were analyzed using descriptive comparative analysis by comparing the results of each cycle. The findings showed that the implementation of the TGT model improved students’ collaboration skills across all indicators, namely active participation, responsibility, flexibility and compromise, and mutual respect among group members. The average percentage of collaboration skills increased from 66.7% in Cycle I to 87.7% in Cycle II. Learning activities involving group discussions, academic games, and tournaments encouraged students to interact more actively, collaborate effectively, and contribute within their groups. Therefore, the TGT learning model is effective in improving students’ collaboration skills in science learning and supports the development of 21st-century competencies.